If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -56a + 90 + 58a = 42 Reorder the terms: 90 + -56a + 58a = 42 Combine like terms: -56a + 58a = 2a 90 + 2a = 42 Solving 90 + 2a = 42 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 2a = 42 + -90 Combine like terms: 90 + -90 = 0 0 + 2a = 42 + -90 2a = 42 + -90 Combine like terms: 42 + -90 = -48 2a = -48 Divide each side by '2'. a = -24 Simplifying a = -24
| (4x+4)=(6x-14) | | (7+n)4=44 | | 7+4(5x+8)=2(2x+1)+5 | | 4(3p*p+2p)-12p*p=2(8p+6) | | 7+n*4=44 | | 7.2-.25=1.8 | | 6b+14=4+4b | | (-2u+3u-5)+(6u+4u+1)= | | (6x+5)+x=26 | | 1.2(x-10)=-2.8(x-9) | | 4+(3i+1)=4i+6 | | -(1-5n)-3(5n+4)=7 | | 6(3z-1)-5(z+4)=5(z+1) | | (3y+10)+y=54 | | 3(s)=48 | | (3x+10)+y=54 | | 4-2x/3=-5x | | 45c+2b= | | 1.9x=16x | | -6(t-7)-(t+2)=8 | | 5/2x-1=1/2-x | | 12x+16=4(3x+4) | | 5/2x-1=1/ | | 5n-1n= | | (5t-5)=3(t+1)+3 | | 3n+10=54 | | -9x-1=3(-3+5) | | 3(2x-7)-(x+12)=5x-33 | | -3(x-7)=0 | | 2+9(x-5)=3-2(x-4) | | 16-2r=3r+2 | | m^3+9m-13=0 |